The Impact of Sei Alalak Bridge Infrastructure for The Community In Alalak Sub-District, Barito Kuala District As A Symbol Of Change From A Historical Perspective - Amelia*, Weni; Rochgiyanti, Rochgiyanti; Prawitasari, Melisa (Riwayat: Educational Journal of History and Humanities, 2024)
Sei Alalak bridge infrastructure is a form of the government's real effort in encouraging the construction of bridges on Trans Kalimantan Road, Alalak District, Barito Kuala Regency, South Kalimantan Province. Its strategic location makes the Sei Alalak bridge not just an ordinary connecting infrastructure. The method used in this research is a literature study with descriptive analysis. The results showed that the impact felt by the community in Alalak District from the Sei Alalak bridge infrastructure as an important link that facilitates movement and increases social interaction between the two communities. In addition, the bridge also facilitates and improves access to health services, education and employment opportunities. Meanwhile, the impact of the Sei Alalak bridge on the community's economy is that it opens up many housing development sites. This encourages some people to plan property investment as a form of long-term investment. In addition, with the widening of the road, the value of land in Alalak District has also increased. As a whole, the Sei Alalak Bridge stands as a symbol of change that reflects economic, social, and cultural progress in the historical development of Banjarmasin and its surroundings. The bridge connects more than just geographical areas; it connects people to new opportunities and a more inclusive social dynamic, carving out a new chapter in the history of the area.